2020
DOI: 10.1111/jnc.15230
|View full text |Cite
|
Sign up to set email alerts
|

The small GTPase Arf6 is dysregulated in a mouse model for fragile X syndrome

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 98 publications
0
2
0
Order By: Relevance
“…43 In mouse model for fragile X syndrome, increased Arf6 activity induces high levels of actin polymerization. 44 Moreover, the ability of Arf6-RhoB complex in coordinating actin cytoskeleton remodeling is central to its role in cancer cell invasion. 45 A previous report in mouse meiosis indicated that Arf6 depletion affected actin filamentmediated spindle movement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…43 In mouse model for fragile X syndrome, increased Arf6 activity induces high levels of actin polymerization. 44 Moreover, the ability of Arf6-RhoB complex in coordinating actin cytoskeleton remodeling is central to its role in cancer cell invasion. 45 A previous report in mouse meiosis indicated that Arf6 depletion affected actin filamentmediated spindle movement.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Arf6 regulates actin cytoskeleton dynamics and membrane trafficking for neuron morphology development and synaptic transmission 43 . In mouse model for fragile X syndrome, increased Arf6 activity induces high levels of actin polymerization 44 . Moreover, the ability of Arf6‐RhoB complex in coordinating actin cytoskeleton remodeling is central to its role in cancer cell invasion 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Circ_0001493, circ_0000487, circ_0001468, and circ_0001345 are spliced from IQ motif and sec7 domain-containing protein 1 (Iqsec1), x-ray repair cross complementing 4 (Xrcc4), homeodomain-interacting protein kinase 2 (Hipk2), and F-box/LRR repeat protein 5 (Fbxl5), respectively, which may be linked to neurocognitive disorders ( Zhang et al, 2013 ; Gerez et al, 2019 ; Liang et al, 2020 ; Briševac et al, 2021 ). Moreover, circ_0001634 originates through back-splicing events from Fam53b, which has been reported to regulate Wnt signal transduction by altering β-catenin nuclear localization ( Kizil et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is an X-linked gene located at Xp11.2. The Sec7 domain in the IQSEC2 protein catalyzes the GDP–GTP exchange on the ARF superfamily of small GTPases (Briševac et al, 2021 ). The IQSEC2 protein is mainly expressed in the brain.…”
Section: Introductionmentioning
confidence: 99%